(3GdEcdjd ef CNHGQ Gdjef hCfSGH MejQs - (3GdMSf Hf CMeO Hf jYbhH GdgeOGfj , GHf GdMGFc , CHh eMeO,J (B334 (3g` s
(3ChdgG (B:s
(3bGd CHh eMeO ChdO cgdGf Hf SHC RjOkG , aChdO RjO heGdckG hZGdHkG s
(3BNQgG (B:s
(3hHjYfG ZhGdjgG HQNU hCQSdfG GdLRGQI ai GdhahO EfbVJ CfSGHge , hEfbVi HEfbVGFgG fSH geOGf , hJUQe Hg cJGH GdEcdjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdLRA GdYGTQs
(3ai eYGQa geOGf hCfSGHgG hYjhf CNHGQgG hgh BNQ GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B204 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B269s
Keywords: (3GdeYGQa GdYGeIs